Free flap surgery in Europe: an interdisciplinary survey. Issue 5 (May 2018) - Rendenbach, C.; Hölterhoff, N.; Hischke, S.; Kreutzer, K.; Smeets, R.; Assaf, A.T.; Heiland, M.; Wikner, J.
Abstract: Free flap surgery is essential for the aesthetic and functional reconstruction of various parts of the body. The aim of this study was to compare current concepts of perioperative flap management between ENT, craniomaxillofacial, and plastic surgeons. A European survey was conducted among 570 surgical departments, covering all aspects of free flap surgery. Focus was placed on antibiotic and antithrombotic drug use, aspects of osseous reconstruction, and flap monitoring strategies. One hundred and seventy-two medical units participated. A broad spectrum of anticoagulant regimens and a trend towards prolonged antibiotic prophylaxis were found. Fixation with (CAD/CAM) reconstruction plates was more popular than monocortical locking with miniplates in the mandible. Visual assessment and Doppler systems were reported to be the most common monitoring modalities. The flap loss rate was stated to be higher after osseous reconstruction. Only a few differences in perioperative flap management were identified between the different surgical fields, and osseous reconstruction appears to be the most challenging.